2009
DOI: 10.1002/cjoc.200990380
|View full text |Cite
|
Sign up to set email alerts
|

Non‐covalent Interaction of Perfluorooctanoic Acid with DNA

Abstract: Health risk from exposure of perfluorochemicals to wildlife and human has been a subject of concern in many fields such as environmental ecology, toxicology, pathology and life sciences. The interactions of perfluorooctanoic acid (PFOA) with DNA were investigated by equilibrium dialysis, circular dichroism and isothermal titration calorimetry techniques under normal physiological conditions in vitro. The binding of PFOA to DNA was a non-covalent interaction and corresponded to the Langmuir adsorption isotherm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Although both PFAAs and PAHs preferentially intercalate into DNA rather than bind to grooves, the tested PFAAs did bind into the minor groove with varying affinities. Intercalation of PFOS and groove binding of PFOA with DNA were reported previously (Li et al 2010;Zhang et al 2009a). In contrast, no groove binding was observed for PAHs.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Although both PFAAs and PAHs preferentially intercalate into DNA rather than bind to grooves, the tested PFAAs did bind into the minor groove with varying affinities. Intercalation of PFOS and groove binding of PFOA with DNA were reported previously (Li et al 2010;Zhang et al 2009a). In contrast, no groove binding was observed for PAHs.…”
Section: Resultssupporting
confidence: 61%
“…Different to the fluorescence displacement data, we observed that PFAAs containing shorter carbon chain lengths give rise to larger DNA conformational changes. Zhang et al studied conformational changes to DNA upon binding PFOA (Zhang et al 2009a). An enhancement in the CD signal at both 245 and 275 nm in the presence of PFOA was observed.…”
Section: Conformational Changes To Dna Upon Interaction With Pfaasmentioning
confidence: 99%
“…In 2009 we identified more than 400 articles after searching Web of Science, PubMed, SciDir and OVID databases using ‘isothermal AND titration AND calorimetry’ or ITC or ‘Isothermal Titration Calorimetry’ search terms. These have been classified into the following categories: Pre‐2009 references cited in the text and review articles 1–43 Protein‐protein and protein‐peptide interactions 44–124 Protein/peptide‐small molecule interactions 125–218 Protein/peptide‐metal ion interactions 219–253 Protein/peptide‐nucleic acid interactions 254–273 Protein/peptide‐lipid interactions 274–292 Protein/peptide‐polysaccharide interactions 293–316 Nucleic acid‐small molecule interactions 317–348 Small molecule interactions …”
Section: Introductionmentioning
confidence: 99%
“…Neither is PFOA a planar molecule capable of intercalation into DNA. Interactions of PFOA with DNA using circular dichroism indicated a change in DNA conformation with the binding to DNA being non-covalent in which PFOA aligned along the backbones and interacted with the homolateral bases via hydrophobic interactions [42] . DNA binding was not found when tested at either 50 (21 μg/mL) or 500 μM (210 μg/mL) concentrations [43] .…”
Section: Discussionmentioning
confidence: 99%